As implicações psicossociais do trabalho precoce de meninos e meninas em condição de rua - Maria de Fátima Pereira Alberto (Universidade do Porto, 2007)
This article concerns the premature work, of street children, involved in the activities of hawking at traffic lights, food vendors, "carguardians"; and girls in the situation of commercial sexual exploitation. It is understood that the interrelation of work conditions and work organization has implications for physical and mental health. We use, as reference, authors who study mental health, work and subjectivity, particularly psychosociology, impairment theory, ergonomics and work psychodynamics. Qualitative methodology is used and four sets of procedures are employed as technique: "territorialization", systematic observation, interviews (individual and group) and lifestories. The results showed that premature insertion is damaging to the lives of these children and adolescents, with psychosocial implications that are noticeable in the following aspects: negative image of themselves and low self-esteem; premature adulthood; absence from school; deviant socialization and a lack of prospects for the future.